Impact of COAP on access to primary care in Ceará and Mato Grosso do Sul through the analysis of interrupted time series - Débora Castanheira Pires; Mônica Rodrigues Campos; Isabel Martins Emmerrick (Universidade de São Paulo, 2021)
ABSTRACT OBJECTIVE: To analyze the impact of implementing the Contrato Organizativo de Ação Pública (COAP - Public Action Organizational Contract) on the expansion of access to primary care in the states of Ceará and Mato Grosso do Sul. METHODS: We used the interrupted time series method to analyze the effect of COAP on primary care coverage (PCCov) and on avoidable hospitalization rates. To analyze the effects of increased PCCov on avoidable hospitalizations, we used non-segmented time series models. RESULTS: The results showed that implementing COAP had a positive impact on increased coverage in both cases, with did not happen in the control states. However, this impact was not reflected in the decrease in hospitalizations due to primary care sensitive conditions (HPCSC) or for acute preventable causes. When we analyzed the effects of the increase in PCCov on avoidable hospitalizations between 2009 and 2016, we observed that coverage had a positive impact on the decrease in the rate of HPCSC only in Ceará, although hospitalizations have a significant trend to decrease in time both in this state and in Mato Grosso do Sul, except for acute respiratory infections. CONCLUSIONS: The COAP continues to be the regulatory instrument of regionalization force, however, the results obtained by adhering to it in the expansion of primary care in Ceará and Mato Grosso do Sul makes us question whether the contractual model, as predicted, is the best instrument for advancing regionalization in the Brazilian Unified Health System.